A DOI Detector With Crystal Scatter Identification Capability for High Sensitivity and High Spatial Resolution PET Imaging - Gu, Z. (IEEE Trans Nucl Sci, 2015)
A new phoswich detector is being developed at the Crump Institute, aiming to provide improvements in sensitivity, and spatial resolution for PET. The detector configuration is comprised of two layers of pixelated scintillator crystal arrays, a glass light guide and a light detector. The annihilation photon entrance (top) layer is a 48 × 48 array of 1.01 × 1.01 × 7 mm(3) LYSO crystals. The bottom layer is a 32 × 32 array of 1.55 × 1.55 × 9 mm(3) BGO crystals. A tapered, multiple-element glass lightguide is used to couple the exit end of the BGO crystal array (52 × 52 mm(2)) to the photosensitive area of the Position Sensitive Photomultiplier Tube (46 × 46 mm(2)), allowing the creation of flat panel detectors without gaps between the detector modules. Both simulations and measurements were performed to evaluate the characteristics and benefits of the proposed design. The GATE Monte Carlo simulation indicated that the total fraction of the cross layer crystal scatter (CLCS) events in singles detection mode for this detector geometry is 13.2%. The large majority of these CLCS events (10.1% out of 13.2%) deposit most of their energy in a scintillator layer other than the layer of first interaction. Identification of those CLCS events for rejection or correction may lead to improvements in data quality and imaging performance. Physical measurements with the prototype detector showed that the LYSO, BGO and CLCS events were successfully identified using the delayed charge integration (DCI) technique, with more than 95% of the LYSO and BGO crystal elements clearly resolved. The measured peak-to-valley ratios (PVR) in the flood histograms were 3.5 for LYSO and 2.0 for BGO. For LYSO, the energy resolution ranged from 9.7% to 37.0% full width at half maximum (FWHM), with a mean of 13.4 ± 4.8%. For BGO the energy resolution ranged from 16.0% to 33.9% FWHM, with a mean of 18.6 ± 3.2%. In conclusion, these results demonstrate that the proposed detector is feasible and can potentially lead to a high spatial resolution, high sensitivity and DOI PET system.